Identification of Single Nucleotide Polymorphism (SNP) in Mono Amine Oxidase A (MAO-A) Gene as a genetic marker for aggressiveness in sheep - Eko Handiwirawan; Ronny R Noor; C Sumantri; Subandriyo .; I Inounu (Indonesian Center for Animal Research and Development (ICARD), 2012)
In the population, there are aggressive sheep in a small number which requires special management those specific animal house and routine management. The purpose of this study was to identify the variation of DNA marker SNP (single nucleotide polymorphism) as a genetic marker for the aggressive trait in several of sheep breed. The identification of point mutations in exon 8 of MAO-A gene associated with aggressive behavior in sheep may be further useful to become of DNA markers for the aggressive trait in sheep. Five of sheep breed were used, i.e.: Barbados Black belly Cross sheep (BC), Composite Garut (KG), Local Garut (LG), Composite Sumatra (KS) and St. Cross Croix (SC). Duration of ten behavior traits, blood serotonin concentrations and DNA sequence of exon 8 of MAO-A gene from the sheep aggressive and nonaggressive were observed. PROC GLM of SAS Ver. 9.0 program was used to analyze variable behavior and blood serotonin concentrations. DNA polymorphism in exon 8 of MAO-A gene was analyzed using the MEGA software Ver. 4.0. The results show that the percentage of the aggressive rams of each breed was less than 10 percent; except for the KS sheep is higher (23%). Based on the duration of behavior, aggressive sheep group was not significantly different with non aggressive sheep group, except duration of care giving and drinking behavior. It is known that concentration of blood serotonin in aggressive and non aggressive rams was not significantly different. The aggressive trait in sheep has a mechanism or a different cause like that occurs in mice and humans. In this study, aggressive behavior in sheep was not associated with a mutation in exon 8 of MAO-A gene. Key Words: Sheep, Aggressive, Exon 8 Of MAO-A Gene, Single Nucleotide Polymorphism